IMROVING THE STUDENTS’ SKILLS OF MUHADHOROH AT MUHAMMADIYAH BOARDING SCHOOL AL MUKHTAR WATUKEBO THROUGH POWER VOICE TECHNIQUES : IMPROVISASI KEMAMPUAN MUHADHOROH SANTRI MUHAMMADIYAH BOARDING SCHOOL AL MUKHTAR WATUKEBO MELALUI TEKNIK POWER VOICE - Huwaida, Hasna' (Khadimul Ummah, 2024)
Islamic da'wah has traditionally been conducted through lectures; the Prophet Muhammad himself served as an example of this practice. It's true that not everyone has the ability to lecture soon after birth. This skill has to be regularly taught and practiced. The goals of the Muhadhoroh operations, which were supported by MBS Al Mukhtar Watukebo, were impeded by a number of issues. Among these are the students' lack of confidence when rehearsing speeches and the speakers' repetitive methods, which make the students bored. This exercise concentrates on these two issues by providing guidance and support for students to improvise their speech abilities in muhadhoroh activities using power voice techniques, a method that is frequently employed. The findings from observations, conversations, and interviews with officials at MBS Al Mukhtar revealed notable shifts in the students' passion and interest in giving presentations. This is in line with the training activities' goals, particularly when using power voice techniques during Muhadhoroh activities.